2012 Information Theory and Applications Workshop 2012
DOI: 10.1109/ita.2012.6181821
|View full text |Cite
|
Sign up to set email alerts
|

Securing inductively-coupled communication

Abstract: Abstract-Communication over inductively-coupled links is becoming prevalent in service delivery for medical, financial, and physical security applications and so there is a growing need to prevent eavesdropping. This paper presents circuittheoretic and communication-theoretic models of inductivelycoupled communication systems. Due to coupling, the presence of an eavesdropper detunes the transfer function between the legitimate users. It is shown this detuning can be detected to reveal the presence of the eaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…where I(X; Y ) denotes the mutual information between X and Y and E[X] the expectation of X with respect to the input probability distribution f X (x). Now, the capacity of H L,T (in bits per symbol) can be obtained by maximizing the fraction in (7) over all input probability distributions f X (x). Note that since the channel is memoryless, it is sufficient to consider only a single use of the channel, i.e., not sequences of length N as in [15,Eq.…”
Section: Channel Capacitymentioning
confidence: 99%
See 3 more Smart Citations
“…where I(X; Y ) denotes the mutual information between X and Y and E[X] the expectation of X with respect to the input probability distribution f X (x). Now, the capacity of H L,T (in bits per symbol) can be obtained by maximizing the fraction in (7) over all input probability distributions f X (x). Note that since the channel is memoryless, it is sufficient to consider only a single use of the channel, i.e., not sequences of length N as in [15,Eq.…”
Section: Channel Capacitymentioning
confidence: 99%
“…, L − 1. Thus, we may substitute f X (L) = 1 − L−1 x=1 f X (x) into (7) and then compute the partial derivatives with respect to f X (x), x = 1, . .…”
Section: Channel Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…The main rationale of these approaches is to trace unique features of RF eavesdroppers in the wireless channel. It showed that the channel state between the legitimate receiver and transmitter changes when an eavesdropper presents due to the near-field inductively coupling [4]. As the near-field coupling is not universal in eavesdropping implementations, a more commonly used feature for detecting eavesdroppers in wireless channels is the local oscillator (LO) leakage level [5][6].…”
Section: Introductionmentioning
confidence: 99%